214k views
5 votes
Which expression is equal to (6x−4)(3x−1)?

2 Answers

2 votes

This is the correct answer according to k12

Which expression is equal to (6x−4)(3x−1)?-example-1
User Kaqqao
by
5.4k points
4 votes

Answer:


(6x-4)(3x-1)  = 18x^2  - 18x + 4 is the required simplification.

Explanation:

Here, the given expression is (6x−4)(3x−1).

By DISTRIBUTIVE PROPERTY of numbers:

A ( B + C ) = AB + AC

Simplifying the given expression, we get:


(6x-4)(3x-1) = 6x(3x-1)-4(3x-1)\\= 6x(3x)  -1(6x)  -4(3x)  +4\\=18x^2  - 6x - 12x + 4\\18x^2  - 18x + 4

or,
(6x-4)(3x-1)  = 18x^2  - 18x + 4

Hence the given expression is simplified.

User Cpuguru
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.